The role of E-WoM in mediating the influence of perceived value and service quality on repurchase intention in fine dining restaurants - Sunarta, Maria Imaculata Louisa; Hariyono, Joseline Grace Cecillia; Dutha, I Dewa Gde Satrya Widya (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2025)
This research aims to analyze and test the role of Electronic Word of Mouth (E-WoM) as a mediating variable in the relationship between Service Quality and Perceived Value on Repurchase Intention in Fine Dining Restaurants. This study uses a quantitative approach, where data is obtained by distributing questionnaires online and the number of samples that were successfully collected and analyzed was 190 people. Data analysis was carried out using Structural Equation Modeling - Partial Least Square (SEM PLS). The results of the study indicate that Perceived Value and Service Quality have a positive effect on Repurchase Intention both directly and indirectly through mediation, namely E-WoM. E-WoM as a mediation also plays a significant role in building people repurchase intentions as well as being an effective means of strengthening the perception of value and quality of Fine Dining Restaurants services.